1993
DOI: 10.1136/bmj.306.6881.827
|View full text |Cite
|
Sign up to set email alerts
|

Residential care for elderly people: a decade of change.

Abstract: 3 Working group on the confidential enquiry into stillbirths and deaths in infancy. Report of the working group set up by the chief medical officer. London:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Thus, a recently reported study of residential care for the elderly in an English health authority area (Stern et al, 1993) found dependency levels to have increased substantially, with the proportion of elderly patients rated as 'dependent' having risen from 34% to 50% between 1979 and 1990, this increase having been most marked among men aged…”
mentioning
confidence: 92%
“…Thus, a recently reported study of residential care for the elderly in an English health authority area (Stern et al, 1993) found dependency levels to have increased substantially, with the proportion of elderly patients rated as 'dependent' having risen from 34% to 50% between 1979 and 1990, this increase having been most marked among men aged…”
mentioning
confidence: 92%
“…Several studies have shown evidence of such an increase [2,3]. Others have considered dependency only in the context of psychiatric morbidity [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Nursing home residents are frailer than community-dwelling older persons, take more different types of medication which are prescribed more frequently and so are particularly at risk of hospitalisation [16][17][18]. A national policy transferring responsibility for continuing care between health, social work and the individual has increased the demand from patients within nursing homes on general practitioners (GPs) and led to a concern about medical care for this group of people with high morbidity and disability, especially with regard to medication use [19][20][21][22][23]. A recent Parliamentary report on the health care of older people 'expressed concern about the inappropriate use of medication in older people, including the over or under-use of medication and the use of medication as a means of controlling patients and residents' [24].…”
Section: Introductionmentioning
confidence: 99%